Sustainable optimization of co-composting horse and chicken manures using response surface methodology (RSM) - Nurin, Arifah Y.; Tee, Tuan P.; Chin, Nyuk L.; Nayan, Nazri (Taylor and Francis, 2025)
The mass production of horse manure (HM) and chicken manure (CM) could be controlled by harnessing their complementary effects via co-composting with sawdust (SW) as bulking agent. Response surface methodology (RSM) was employed to analyze the influence of four independent factors: HM:CM composition (HM:CM), particle size (PS), composting period (CP), and bulking agent amount (BAA) on nine quality parameters. The results showed significant effects on carbon-to-nitrogen (C/N) ratio, nitrogen (N), potassium (K), dry matter, moisture content, and bulk density but not on organic matter, phosphorus, and pH value. The optimum condition was obtained with 87:13 for HM:CM (%), PS of 0.5 cm, 32 days of CP with 20% of sawdust producing C/N ratio of 20.1, 2.1% N and 1.3% K. HM and CM co-compost that meets the desired quality for agricultural use can be achieved through the models derived from RSM optimization.